2007
DOI: 10.1055/s-2007-976168
|View full text |Cite
|
Sign up to set email alerts
|

The Double Hazard of Thrombophilia and Bleeding in Acute Promyelocytic Leukemia

Abstract: Acute promyelocytic leukemia (APL), once highly fatal, has emerged as the most curable subtype of acute myeloid leukemia in adults. Cure is now expected in approximately 70 to 90% of patients when treatment includes all- TRANS retinoic acid (ATRA) combined with anthracycline-based chemotherapy. Early mortality most often is due to a severe and often catastrophic bleeding, often intracerebral in location, and remains a major cause of treatment failure. Thrombosis, either at diagnosis or during the course of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 74 publications
0
36
0
3
Order By: Relevance
“…APL is well known for its coagulopathy and high susceptibility to all-trans retinoic acid (ATRA) [1,2]. Our previous study revealed that 77.6% of patients had overt disseminated intravascular coagulation (DIC) upon diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APL is well known for its coagulopathy and high susceptibility to all-trans retinoic acid (ATRA) [1,2]. Our previous study revealed that 77.6% of patients had overt disseminated intravascular coagulation (DIC) upon diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically significant bleeding occurred in 22.4% and fatal bleeding in 11.2% of patients [3]. Although the major threat of APL is severe bleeding complications in the early phase [3,4,5,6], patients with APL are also prone to thrombosis [1,2,7,8]. Both arterial and venous thrombosis may occur in APL.…”
Section: Introductionmentioning
confidence: 99%
“…40 APL is a special subtype of acute myeloid leukemia whose biologic and clinical features include the presence of the specific t(15;17) chromosomal translocation in leukemic blasts and the frequent existence of severe hemorrhagic diathesis at the time of diagnosis. [106][107][108] The mechanism for the hemorrhagic deaths partially involves hyperfibrinolysis, which occurs because of the excessive production of plasmin at the surface of the promyelocytic leukemic cells. 109 We observed that depletion of S100A10 from the APL cell line, NB4, which constitutively expresses the PML-RAR-␣ oncoprotein, resulted in a 70% loss in plasminogen binding and a 64% loss in plasmin generation by the NB4 cells.…”
mentioning
confidence: 99%
“…The pathogenesis of coagulopathy is complex and is a manifestation of disseminated intravascular coagulation, primary fibrinolysis and direct proteolysis. 43 ATRA should be initiated at the earliest suspicion of the disease without waiting for cytogenetic or molecular confirmation. Aggressive blood product support to maintain the platelet count ≥ 30,000 to 50,000/μL and the fibrinogen level at ≥ 150 mg/ dL has been recommended.…”
Section: Reducing Early Death In Aplmentioning
confidence: 99%